Saving Africa’s Children: Transnational Adoption and The New Humanitarian Order - Olutola, Sarah (My University, 2017)
My dissertation explores transnational adoptions of black African children by white Western parents as a site through which to think about global affective relationality and transnational histories within intimate proximities. The image of an interracial, transnational family can seem to be a fulfillment of the potential for transcendent love symbolized by humanitarian fundraisers such as Live Aid— a love that collapses borders and brings together races in multicultural bliss. Furthermore, adoptions of African children can potentially challenge discursive systems of categorization that frame the black body as existing outside the body politic. At the same time, however, we cannot understand transnational adoption without taking into account the histories of power that make possible and potentially limit the contours of these affective orientations. Indeed, representations of a transnational family consisting particularly of black African children and white Western parents not only invoke the logic of white moral motherhood within the context of contemporary globalization; they also point to European philosophical traditions that presuppose the colonizer’s right to the black body. In this project, thus, I ask: what are the sociopolitical and cultural motivations behind the desire to express humanitarian love towards African children through the act of adoption? How might these motivations create avenues for exclusion and exploitation even as they create new geographies of belonging? To answer these questions, this project brings the affective domain of contemporary transnational adoption between African children and white American parents into conversation with histories of colonial transnational intimacies and the precarious lived experiences of classed and racialized individuals in the African postcolony. In challenging popular celebratory fictions of the transnational family, it critically examines not only the utopian aspirations and social costs of transnational adoption as a humanitarian project, but also the very affect produced and channeled through adoption as a humanitarian act.
This PhD Dissertation was completed through 2011 to 2016 and was nominated for a CAGS-UMI Distinguished Dissertation Award.
Keywords: transnational adoption; youth and childhood studies; globalization; African Studies; postcolonialism; critical race studies; multiculturalism; motherhood; affect; intimacy; Bildungsroman; citizenship; nineteenth century; twentieth century; twenty-first century; angelina jolie; celebrity studies; olympics; black mothers; African mothers; missionaries; Mary Slessor; Victorian literature; transnational adoptees; human trafficking; slavery; Ethiopia; Nigeria